Fabric authenticity method using fast Fourier transformation detection - Norislina, Ismail; Wan Muhammad Syahrir, Wan Hussin; Jasni, Mohamad Zain; Tao, Hai (IEEE, 2011)
The authenticity or originality of sport jersey cloth fabric in market nowadays is difficult to distinguish. This is a critical issue that leads to the difficulty for customer to know whether they are purchase the original fabric or the fake one. The purpose of this paper is to develop a prototype for Fabric Authenticity System to judge the originality of jersey cloth fabric based on its pattern structure. Besides this, this study aimed to identify the image processing technique which is Fourier analysis to differentiate the authentic and artificial fabric. As a result, the originality of the fabric can be detected based on the fabric pattern structure itself by looking on its Fourier spectrum.